Written corrective feedback in English for specific purposes nursing students' writing courses: A quasi-experimental study - Milad Ramazani (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: In the field language, teaching Written Corrective Feedback (WCF) has attracted considerable attention as a beneficial pedagogical technique. The present study aimed to determine the short-term and long-term effectiveness of WCF strategies for ameliorating English for Specific Purposes (ESP) nursing students' writing ability in English nursing reports. Materials & Methods: In this quasi-experimental study, the researcher employed convenience sampling to select 93 intermediate-level learners from three intact classes at a university of medical sciences in Iran as participants based on their results on the Oxford Placement Test. The researcher then assigned these classes to three experimental groups, including direct WCF, indirect WCF, and meta-linguistic WCF groups. He administered a writing pre-test to all groups. Subsequently, each of these groups received their pertinent WCF treatment in 10 sessions. Following the completion of the treatment, a post-test was administered to all of the groups. The researcher conducted a follow-up test one month after the post-test. Finally, SPSS 24 was used to analyze the data. Results: The results highlighted the fact that the meta-linguistic WCF proved more effective than the direct and indirect WCF strategies (p < 0.05. Furthermore, the direct WCF strategy had a more positive effect on the ESP nursing students' writing ability in comparison with the indirect WCF strategy (p < 0.05). Conclusion: These results may provide the ESP teacher educators, syllabus designers, and instructors guiding principles regarding the use of WCF in ESP nursing students' writing courses.